The Legalization of Interfaith Marriage in Indonesia (Between Universalism and Cultural Relativism) - Muhammad Ihsan Firdaus (Eastasouth Institute, 2023)
In the context of positive law in Indonesia, interfaith marriage is not recognized, because according to Article 2 paragraph (1) of Law Number 1 of 1974 concerning Marriage, it is explained that a valid marriage is based on the laws of each religion and belief. However, this is not enough to accommodate the development of marriage law in Indonesia, such as in the case of Judgement Number 508/Pdt.P/2022/PN JKT.SEL whose gives permission to applicants who are bound by marriage but of different religions to register their marriage at South Jakarta Department Population and Civil Registration Agency. So based on this, this research aims to find out how the concept of universalism and cultural relativism is in the context of interfaith marriage and how is the legalization of interfaith marriage in Indonesia in the context of marriage as one of the non-derogable human rights. This research uses legal research methods. So that the results of this research found that, first, interfaith marriages in Indonesia still do not have clear and firm regulations, giving rise to legal uncertainty and legal vacuum, the principle of universalism is more relevant in the context of interfaith marriages in Indonesia than the cultural relativism concept. Second, the state can issue an Interfaith Marriage Book as a form of legalizing interfaith marriages in Indonesia and providing legal certainty.